Inflação e retornos acionários - Chaves, Carlos Roberto Simões (2017)
This paper examines the impact of expected inflation on stock returns and earnings per share projections for the next 12 months. We used the Ibovespa's weekly real returns and FOCUS survey for IPCA and Industrial Production growth. A one-percentage point increase in projected inflation over the next 12 months is associated with a decline of 0.56 percentage points in the weekly Ibovespa real change to a significance level of 1%. No statistically significant relationships were found between the expected inflation and the projections for Ibovespa's profits. It was verified that the Ibovespa's weekly returns also react negatively to the 5-year CDS oscillations and the VIX index.